2021
DOI: 10.1108/jmp-12-2019-0677
|View full text |Cite
|
Sign up to set email alerts
|

Work-related use of information and communication technologies after hours and employee fatigue: the exacerbating effect of affective commitment

Abstract: PurposeWork-related use of information and communication technologies (ICTs) after hours can be potentially detrimental to employee well-being. In the current study, we examine whether psychological detachment mediates the link between work-related use of ICTs after hours and fatigue and whether affective commitment exacerbates this mediated relationship.Design/methodology/approachWe collected two waves of data from 295 employees in Vietnam, with 51% being female and an average age of 37.81 years old (SD = 7.9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(38 citation statements)
references
References 35 publications
5
33
0
Order By: Relevance
“…Similarly, organisational ICT use was also found to be denoted by digital skills and competences of employees in the context of national ICT use (Yunis et al, 2012). In this sense, relevant indicators can be related to the number of staff trained for handling ICTs (Cuevas-Vargas et al, 2016), the percentage of personnel with ICT skills (Giotopoulos et al, 2017) or work-related use of ICTs after hours (Lee et al, 2021).…”
Section: Approaches To Organisational Ict Implementationmentioning
confidence: 98%
“…Similarly, organisational ICT use was also found to be denoted by digital skills and competences of employees in the context of national ICT use (Yunis et al, 2012). In this sense, relevant indicators can be related to the number of staff trained for handling ICTs (Cuevas-Vargas et al, 2016), the percentage of personnel with ICT skills (Giotopoulos et al, 2017) or work-related use of ICTs after hours (Lee et al, 2021).…”
Section: Approaches To Organisational Ict Implementationmentioning
confidence: 98%
“…As mentioned earlier, W_ICTs refers to the use of information and communication technology (e.g., smartphones or laptops) to handle work-related tasks before and after hours or during breaks (Lee et al, 2021 ; Piszczek, 2017 ; Xie et al, 2018 ). With the development of information and communication technology, W_ICTs becomes very common, so employees can handle work anytime and anywhere (Xie et al, 2018 ).…”
Section: Theory and Hypothesesmentioning
confidence: 99%
“…Emotional exhaustion refers to the fatigue caused by excessive consumption of mental and emotional resources (McDowell et al, 2019 ; Yao et al, 2020 ). Some studies have found that W_ICTs will make employees consume their resources to deal with the work, which will exert a negative impact on their psychological detachment (Lee et al, 2021 ; Sonnentag & Fritz, 2015 ). By physically and mentally “switching off” from work after hours, employees can restore their depleted resources from job stressors and maintain their health and well-being (Lee et al, 2021 ).…”
Section: Theory and Hypothesesmentioning
confidence: 99%
See 2 more Smart Citations